A dynamic incentive mechanism for transmission expansion in electricity networks: Theory, modeling, and application - Juan Rosellón; Hannes Weigt (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
We propose a price-cap mechanism for electricity-transmission expansion based on redefining transmission output in terms of financial transmission rights. Our mechanism applies the incentive-regulation logic of rebalancing a two-part tariff. First, we test this mechanism in a three-node network. We show that the mechanism intertemporally promotes an investment pattern that relieves congestion, increases welfare, augments the Transco's profits, and induces convergence of prices to marginal costs. We then apply the mechanism to a grid of northwestern Europe and show a gradual convergence toward a common-price benchmark, an increase in total capacity, and convergence toward the welfare optimum.
Keywords: L51; L91; L94; Q40; 330; Electricity transmission expansion; incentive regulation; Stromnetz; Infrastrukturinvestition; Anreizregulierung; Elektrizitätswirtschaft; Energieverbund; Netzzugang; Theorie; Westeuropa